Role of Pregabalin in Management of Pruritus: A Literature Review - Nazanin Foroutan; Naemeh Nikvarz (Frontiers Media S.A., 2016)
Pruritus can be one of the distressing symptoms of many dermatologic, systemic, neurologic or psychiatric disorders. In each case, the origin of itch is in the skin and/or the nervous system. Involvement of the nervous system causes neurogenic, psychogenic or neuropathic itch. Itch sensation is transferred to the central nervous system via unmyelinated C-type nerve fibers, and many mediators and receptors engage in the its induction and transmission. Also it has been demonstrated that there are similarities and interactions between neurotransmitters and pathways of pain and itch sensation. Hence, effective drugs in reducing the neuropathic pain such as pregabalin have been studied and used in the management of different itchy conditions.  In this narrative review we considered the available published papers dealing with the antipruritic effects of pregabalin. Results of studies conducted in uremic patients show that pregabalin is an effective option in reducing uremic pruritus especially in those who have not responded to antihistamines and topical moisturizers. Data about the effects of pregabalin on other itchy conditions are very limited; however results of the available studies show beneficial effects of this drug in burn patients with more than 5% involvement of the total body surface area, in prurigo nodularis, and in chronic and idiopathic itch. One considerable issue is that the therapeutic effects of pregabalin on uremic pruritus and post burn itch may appear more rapidly than its effects in the other conditions (1-2 weeks vs > 4 weeks). The most reported adverse effects of pregabalin are sedation, dizziness and drowsiness. Whether pregablin can be unequivocally considered as an effective and reasonable choice in the management of pruritus with different causes is a question that should be answered through large scale randomized controlled studies.